Knowledge and Attitude on Human Immunodeficiency Virus among Migrant Worker Candidates in East Java, Indonesia - Faiz Murfid Gunawan; Pudji Lestari; Erwin Astha Triyono (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: In 2018, East Java province becomes the province with the highest number of Human Immunodeficiency Virus (HIV) cases in Indonesia with an incidence of more than 8,000 cases. This province has various groups of Indonesian Migrant Workers (Tenaga Kerja Indonesia, TKI) working in various sectors in different countries, making them prone to HIV infection. This study aimed to determine the level of knowledge and attitude towards HIV and Acquired Immune Deficiency Syndrome (AIDS) among migrant worker candidates in East Java.Methods: This was a cross-sectional descriptive study conducted in August 2018 in the Provincial Manpower and Transmigration Office of East Java, Indonesia. The knowledge and attitude towards HIV disease were assessed using a self-validated questionnaire distributed to 104 migrant worker candidates as the subjects of this study.Results: Eighty-nine percent of the subjects had good knowledge, while 98% of them had good attitudes towards HIV disease. Furthermore, 86% had good attitudes toward HIV transmission. However, no correlation was observed between the subjects’ level of knowledge and their attitude (p=0.334).Conclusions: In general, the level of knowledge and attitudes of migrant worker candidates in East Java towards HIV disease is good. Nevertheless, more knowledge and education on healthy behavior need to be envisaged for this group.